MENINGKATKAN MINAT BELAJAR FISIKA SMP DAN SMK NUSA BHAKTI SAWANGAN DEPOK MELALUI TEKNOLOGI MEDIA ROBOTIK - Setia Asih, Dwi Aprillia; Okyranida, Indica Yona; Aqil, Deden Ibnu (Jurnal Terapan Abdimas, 2019)
Abstract. In order to increase the interest in learning physics in SMP and SMK Nusa Bhakti Sawangan Depok through robtik media, an introduction was made to the making of robotic media using line follower and robot soccer robots. The method used is to provide information in making robotic media line follower and robot soccer robots. The material provided during the workshop included the creation, management and utilization of learning media in the form of robotic media. After the activity was finished the students were given a questionnaire to determine the response of students' interest in the learning media used. From the results of this activity the results of student responses to learning media used in good categories are seen from the total score of all students, namely 1098 from the total score of 1500, in other words the interest in learning physics increases when learning activities use line follower robots and robot soccer as learning media . Then the students were enthusiastic during the activity, listening and paying attention to the explanation of the community service team and being active and happy during the process of the experimental activities. And teachers can also use robotic media to be an alternative learning media.Abstrak. Dalam rangka meningkatkan minat belajar fisika SMP dan SMK Nusa Bhakti Sawangan Depok melalui media robtik, dilakukan kegiatan pengenalan  pembuatan media robotik menggunakan robot line follower dan robot soccer. Metode yang digunakan adalah memberikan informasi dalam membuat media robotik robot line follower dan robot soccer. Materi yang diberikan saat workshop memuat pembuatan, pengelolaan, dan pemanfaatan media pembelajaran  dalam bentuk media robotik. Setelah kegiatan selesai siswa diberikan angket untuk mengetahui respon minat siswa terhadap media pembelajaran yang digunakan. Dari hasil kegiatan ini didapatkan hasil respon siswa terhadap media pembelajaran yang digunakan dalam kategori baik dilihat dari jumlah skor seluruh siswa yaitu 1098 dari jumlah skor maksimm 1500, dengan kata lain minat belajar fisika meningkat saat kegiatan pembelajaran menggunakan robot line follower dan robot soccer sebagai media pembelajaran. Kemudian Siswa antusias selama kegiatan berlangsung, mendengarkan dan memperhatikan penjelasan tim pengabdian masyarakat serta aktif dan gembira selama proses kegiatan eksperimen. Dan guru juga dapat menggunakan media robotik menjadi salah satu alternatif media pembelajaran.